SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN BUAH RAMBUTAN DENGAN KUALITAS TERBAIK MENGGUNAKAN METODE WEIGHTED PRODUCT (WP) - Yosa`aro Zai; Mesran Mesran; Efori Buulolo (STMIK Budi Darma, 2017)
Decision support systems are generally defined as a system capable of producing solutions and problem-solving. Decision support systems are not intended to replace decision-making roles, but to assist and support decision makers. In the role of decision support systems in the overall context of information systems aimed at improving performance through the application of information technology and determine the approach used in the decision-making process, to evaluate the interactive selection. One of the most commonly used methods in decision support systems is the Weighted Product (WP) method.